Gas turbine sub-idle performance modelling : altitude relight and windmilling - Zachos, Pavlos K. (Cranfield University, 2010)
Sub-idle is a very challenging operating region, as the performance of a gas tur¬bine engine changes significantly compared to design conditions. In addition, the regulations for new and existing engines are becoming stricter and the prediction of engine’s relight capability is essential. In order to calculate the sub-idle performance of an engine, detailed component representation is required. The data obtained from rig tests is usually insufficient at the low speeds. This creates the need for further research about component behavior within the sub-idle regime before any whole engine relight performance prediction is attempted. Within this research, the sub-idle compressor map generation methodologies are pushed a step forward by the definition of the zero-speed curve, that is the low¬est speed line of a compressor map. In this way the sub-idle characteristic can be interpolated between the zero-speed line and the above-idle given speed lines. Con¬sequently, the generation of the characteristic within the whole range of operation is allowed. In addition, the sub-idle and relight combustion modelling is enhanced by a novel combustion model which accounts for fuel evaporation effects. The de¬velopment of such a model is based on the fact that fuel evaporation effects have a significant impact on the combustion efficiency during the engine relight manoeu¬vres. Finally, the sub-idle exhaust mixing phenomena are investigated as the relight modelling of a mixed exhaust engine cannot be carried out using the conventional approaches as there is a non-negligible difference between the pressures of the two coaxial jets. The models generated by the component related research are partially integrated within the relight performance simulation solver BD19 in order for whole engine performance simulations to be carried out. More specifically, the windmilling and the groundstarting performance of a modern, civil, high bypass ratio engine is examined. The current thesis contributes to knowledge both at component as well as at whole engine performance prediction levels. As far as sub-idle compressor perfor¬mance is concerned, a generic pressure loss model for compressors operating at highly negative incidence angles has been developed. It is validated against experimental data and is applicable on every compressor with given design parameters. In addi¬tion, the new combustion model allows for a more accurate combustion efficiency prediction during the relighting processes while the research on mixed exhaust en¬gine configurations enhances the physical background of the sub-idle mixing process allowing for a more efficient performance modelling. The physics based component related research, in overall, offers significant benefits to the sub-idle and relight per-formance modelling of gas turbines increasing its predictive capability and therefore the reliability of the current and future aero engines.